Sonographically Guided Core Biopsy: A Minimally Invasive Procedure for Managing Adnexal Masses. (1st November 2013) - Oge, Tufan; Yalcin, Omer T.; Ozalp, S. Sinan; Kebapci, Mahmut; Aydin, Yunus; Telli, Elcin
Abstract : Objectives: We hypothesized that sonographically guided core biopsy is an effective method for the differential diagnosis of adnexal masses and evaluated patients who underwent core biopsies in our gynecologic oncology department. Methods: We reviewed the medical records of 55 patients who underwent sonographically guided core biopsies in our gynecologic oncology department between 2010 and 2013. Patients with suspected ovarian malignancies who were unsuitable for optimal debulking surgery and patients at risk for higher morbidity and mortality because of a poor performance status, suspected nongynecologic tumors, and peritoneal tuberculosis were indicated for sonographically guided biopsy. Results: The indications for sonographically guided core biopsy were candidacy for suboptimal cytoreduction (n = 32 [58.2%]), a poor performance status (n = 11 [20.0%]), and suspected nongynecologic tumors (n = 12 [21.8%]). Histopathologic evaluations revealed primary ovarian tumors in 36 patients (65.5%). Tuberculosis was found to be the second most common disease (n = 8 [14.5%]) among the patients who underwent core biopsies. In 2 patients (3.6%), histologic examination revealed metastatic colorectal cancer. Conclusions: Sonographically guided core biopsy may be preferred as a minimally invasive procedure for managing adnexal masses, particularly in patients with advanced ovarian cancer and high comorbidities who might benefit from neoadjuvant chemotherapy and in cases of suspected nongynecologic tumors, including pelvic tuberculosis.